ChemInform Abstract: Copper Salt of 12‐Tungstophosphoric Acid: An Efficient and Reusable Heteropoly Acid for the Click Chemistry. Issue 44 (14th October 2013) - Purnima, K. V.; Sreenu, D.; Bhasker, N.; Nagaiah, K.; Lingaiah, N.; Reddy, B. V. Subba; Yadav, J. S.
Abstract The catalyst can be recovered and reused for three to four subsequent runs with a minimal decrease of activity.